1996
DOI: 10.1089/dna.1996.15.1121
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Sequence Analysis of the Human MG160, a Fibroblast Growth Factor and E-Selectin Binding Membrane Sialoglycoprotein of the Golgi Apparatus

Abstract: The amino acid sequence of MG160, a membrane sialoglycoprotein of the medial cisternae of the rat Golgi apparatus, is more than 90% identical with CFR, a fibroblast growth factor (FGF) binding protein of chicken membranes, and with ESL-1, a ligand for E-selectin of plasma membranes of myeloid cells; furthermore, MG160, isolated by immunoaffinity chromatography from rat brain membranes, binds to basic FGF. The gene for MG160 has been assigned to human chromosome 16q22-23. To characterize this protein further in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
5
18
0
Order By: Relevance
“…Quantitative electron microscopy and immunocytochemical analysis of p79ER-expressing rat fibroblasts (FR3T3-316) confirmed the localization of p79ER in structures morphologically indistinguishable from those labelled for the ER membrane protein marker calnexin. This revealed that more than 75 % of anti-p79 gold labelling was located in the ER compartment and almost 15 % was located in the Golgi apparatus, where MG-160-like proteins are mainly localized [15,18,35]. These data could suggest a rapid recycling of p79ER between the ER and the Golgi, with an accumulation of p79 in the ER, as previously described for other proteins [36,37].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Quantitative electron microscopy and immunocytochemical analysis of p79ER-expressing rat fibroblasts (FR3T3-316) confirmed the localization of p79ER in structures morphologically indistinguishable from those labelled for the ER membrane protein marker calnexin. This revealed that more than 75 % of anti-p79 gold labelling was located in the ER compartment and almost 15 % was located in the Golgi apparatus, where MG-160-like proteins are mainly localized [15,18,35]. These data could suggest a rapid recycling of p79ER between the ER and the Golgi, with an accumulation of p79 in the ER, as previously described for other proteins [36,37].…”
Section: Discussionsupporting
confidence: 72%
“…Previously, only CFR and MG-160 have been shown to bind FGF-2 [11,15]. Zhou et al [39] have shown that CFR possibly harbours two distinct FGF-binding sites ; one of these is heparin-dependent, whereas the other is not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Chinese hamster ovary cells (CHO), CFR-1 was found to be expressed only in the Golgi apparatus (Burrus et al, 1992), but it can also be secreted in a mutated form (Zuber et al, 1997). Depending on the organism, two detected variants of CFR-1, ESL-1 and MG-160, share sequence homologies between 88% and 95% (Burrus et al, 1992;Mourelatos et al, 1996;Steegmaier et al, 1995;Stieber et al, 1995) and do not appear to share any sequence homologies to other known proteins. Function and cellular distribution of CFR-1 and the homologues is relatively unknown and contradictory.…”
Section: Hensel Et Almentioning
confidence: 99%